Cryo-electron microscopy structure and densities of a pentameric ligand-gated ion channel GLIC - Rovsnik, Urska; Howard, Rebecca; Bergh, Cathrine; Lindahl, Erik (Stockholm University, 2023)
This Dataset contains cryo-electron microscopy (cryo-EM) densities and a pdb model of a Gloeobacter violaceus ligand-gated ion channel (GLIC). The densities were generated with RELION data processing software and the model was built with COOT software. Additionally the dataset contains a validation report generated by PDB/EMDB deposition webpage, where the data has been uploaded and is currently on hold until publication of the paper (https://deposit-pdbe.wwpdb.org/deposition).

The densities, the model and the validation report were requested by reviewers for a publication titled 'Discovery of lipid binding sites in a ligand-gated ion channel by integrating simulations and cryo-EM' currently accesible on Biorxiv and under review at eLife.
Keywords: Structural biology (incl. macromolecular modelling); Signal transduction; Proteins and peptides; Medical and Health Sciences; Medicin och hälsovetenskap; Structural Biology; Strukturbiologi